Prawa człowieka w prawie i praktyce Mercosur - Gałka, Katarzyna (Kwartalnik Prawa Publicznego, 2017)
This article analyzes a gradual, but increasingly intense, process of inclusion human rights into the system of the Common Market of the South (hereinafter: Mercosur). The article aims to present the course and basic elements of the process and to answer the questions concerning the motives, nature and scope of activities undertaken in its framework. The analysis also allowed to distinguish basic characteristics (specific features) of the process of incorporating human rights into the Mercosur system. These include: the lack of a Mercosur instrument containing a catalogue of human rights; striving for unification of standards and coordination of Member States’ policies as a goal for Mercosur in the field of human rights; a strong link between human rights and democracy, as well as the failure to develop human rights instruments of a transnational nature. Against the background of all the findings made, the article also seeks for a general assessment of the process of incorporation of human rights into the Mercosur system from two perspectives, namely the integration law and human rights law. In the first case, the article puts forward the argument that the effect of incorporating human rights into the Mercosur framework is a change in the paradigm of States’ integration in the common market of South America. It is reflected in the content of certain Mercosur legal acts, such as the decision of the Council of Common Market No. 14/09, according to which a consolidation of rights human is the „fundamental axis of identity and development” of this organization. This is also evidenced by the application of article 5 of the Ushuaia Protocol to Venezuela. However, this change is not yet fully established, and - looking from the perspective of human rights law - the actions and measures taken within Mercosur to promote and protect human rights are not currently sufficiently developed and coherent to be considered as forming a system. Some of the solutions adopted may, however, give rise to the development of effective human rights guarantees in the future.